Effect of working capital policies on firms' financial performance - Randa Mohammed Shams Addin Al-Mawsheki (Cogent Economics & Finance, 2022)
This study focuses on short-term investment and financing decisions influenced by a firm's working capital policy and the effect of working capital policies on the financial performance of manufacturing firms in Malaysia. Working capital policies were measured by working capital financing and investment policies. Working capital investment policy was measured by the ratio of current assets to total assets. Working capital financing policy was categorized as conservative working capital financing policy, aggressive working capital financing policy, and matching working capital financing policy. This study considered matching working capital financing policy, which was not considered in previous empirical studies. The data included 147 firms with 1470 firm-year observations for the period from 2010 to 2019. The results revealed that the current asset to total asset ratio significantly negatively affected firms' financial performance. Meanwhile, a conservative working capital financing policy was positively and significantly related to a firm's financial performance. The finding implies that Malaysian manufacturing firms can increase their operating income by adopting an aggressive working capital investment policy. The finding also implies that Malaysian manufacturing firms can increase their operating income by implementing a conservative working capital financing policy rather than a matching or an aggressive working capital financing policy.
Keywords: 330; Conservative; aggressive; matching; working capital financing policy; Malaysia; manufacturing firms